2014
DOI: 10.1186/1471-2229-14-11
|View full text |Cite
|
Sign up to set email alerts
|

Tissue specific analysis reveals a differential organization and regulation of both ethylene biosynthesis and E8 during climacteric ripening of tomato

Abstract: BackgroundSolanum lycopersicum or tomato is extensively studied with respect to the ethylene metabolism during climacteric ripening, focusing almost exclusively on fruit pericarp. In this work the ethylene biosynthesis pathway was examined in all major tomato fruit tissues: pericarp, septa, columella, placenta, locular gel and seeds. The tissue specific ethylene production rate was measured throughout fruit development, climacteric ripening and postharvest storage. All ethylene intermediate metabolites (1-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 57 publications
2
35
0
1
Order By: Relevance
“…Taken together, an extensive understanding of the nature of plant–pathogen interaction under drought stress would be needed in cases where trichomes enhance pathogen growth. Mapping for leaf pubescence related QTLs have been done for many plants like Gossypium hirsutum and A. thaliana (Lacape and Nguyen, 2005; Bloomer et al, 2014). It can be hypothesized that enhancement of trichome production impart protection against combined drought and pathogen infection in many cases and trichomes can be considered as a potential morpho-physiological trait conferring tolerance to the stress combination.…”
Section: Potential Traits For Screening Genotypes For Tolerance To Comentioning
confidence: 99%
“…Taken together, an extensive understanding of the nature of plant–pathogen interaction under drought stress would be needed in cases where trichomes enhance pathogen growth. Mapping for leaf pubescence related QTLs have been done for many plants like Gossypium hirsutum and A. thaliana (Lacape and Nguyen, 2005; Bloomer et al, 2014). It can be hypothesized that enhancement of trichome production impart protection against combined drought and pathogen infection in many cases and trichomes can be considered as a potential morpho-physiological trait conferring tolerance to the stress combination.…”
Section: Potential Traits For Screening Genotypes For Tolerance To Comentioning
confidence: 99%
“…It is therefore possible that system 2 ethylene production is not the only mechanism contributing to the autocatalytic regulation of climacteric ethylene. Recent data showed that ethylene biosynthesis displays a tissue-specific and developmental differentiation throughout tomato fruit growth, indicating that it is organized and regulated in a well-defined tissue-specific way (Van de Poel et al, 2014).…”
Section: Ethylene Biosynthesis Is Instrumental To Climacteric Fruit Rmentioning
confidence: 99%
“…A targeted metabolomics and proteomics study by Van de Poel et al (2014b) investigated the tissue specificity of the ethylene biosynthesis pathway in tomato fruit. They observed that the pericarp tissue produced the highest amount of ethylene (and high ACO activity), while the pericarp had the lowest ACS activity and ACC content compared to other tissues.…”
Section: Acc Transport and Its Role During Root Stressmentioning
confidence: 99%